THE SYMBIOTIC EVOLUTION: LANGUAGE AND ARTIFICIAL INTELLIGENCE (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
The relationship between language and Artificial Intelligence (AI) is one of deep interdependence and accelerating change. AI, particularly through Natural Language Processing (NLP) and Large Language Models (LLMs), didn't just borrow from human language; it is now actively transforming its acquisition, use, and structure. This thesis reviews this symbiotic connection, highlighting the immense opportunities AI offers in areas like personalized language education and global accessibility, while critically examining the complex challenges stemming from inherent linguistic ambiguity, data bias, and ethical deployment. The overall trajectory points toward a closer future integration that necessitates a balanced approach, one that harnesses the computational power of AI without sacrificing the essential nuance and critical human interaction embedded in language.